The influence of grip width on training volume during the bench press with different movement tempos - Wilk, M.; Gepfert, M.; Krzysztofik, M.; Golas, A.; Mostowik, A.; Maszczyk, A.; Zajac, A. (Journal of Human Kinetics, 2019)
The aim of the study was to determine the effect of the wide-grip bench press (WGBP) and the close-grip bench press (CGBP) on the number of performed repetitions (REPs) and time under tension (TUT) using a variable tempo of movement. Twenty (20) women experienced in resistance training were enrolled in the study (1RM-CGBP = 55.2 ± 9.5 kg; 1RM-WGBP = 52.7 ± 8.5 kg). Participants performed 5 sets of the BP with a maximal number of REPs at 70%1RM. Different tempos of movement, i.e., slow (6/0/X/0) and fast (2/0/X/0), and grip widths, i.e., the CGBP and the WGBP, were employed. The following variables were registered: maximal number of repetitions in every set (REPSet1-5), total number of repetitions performed in 5 sets (TREP), maximal time under tension in every set (TUTSet1-5) and total time under tension in 5 sets (TTUT). The two-way ANOVA revealed statistically significant differences between the WGBPFAST and the WGBPSLOW in TUTSet1-5 (p < 0.05) and TTUT (p < 0.01), as well as between the CGBPFAST and the CGBPSLOW in TUTSet1-5 (p < 0.01) and TTUT (p < 0.01). Significant differences between the WGBPFAST and the WGBPSLOW were also observed in REPSet1-5 (p < 0.01) and TREP (p < 0.01) as well as between the CGBPFAST and the CGBPSLOW in REPSet1-5 (p < 0.01) and TREP (p < 0.01). No significant differences between the WGBPSLOW and the CGBPSLOW nor the WGBPFAST and the CGBPFAST were found. The study demonstrates that the tempo of movement, regardless of the width grip, has a significant effect on the volume of effort in resistance training.